Two cultures essays in honour of David Speiser - Williams, Kim (Birkhäuser Basel, 2006)
David Speiser is Professor Emeritus at the Catholic University of Louvain, where he taught mathematics and physics from 1963 to 1990. His work in history of science included various publications, some of which are related to art history. Nephew of mathematician Andreas Speiser, David Speiser's own wide-ranging interests have brought him into contact with a panorama of disciplines. Editor Kim Williams has assembled a group of notes where scholars contribute essays inspired by their contact with Prof. Speiser in honour of his eightieth birthday. Topics range from history of sciences to history of art, from architecture theory to music theory, from particle physics to the proliferation of nuclear weapons, to an essay on the very nature of interdisciplinary studies. Contributors: Alessio Ageno, Jean-Pierre Antoine, Sandro Caparrini, Frans A. Cerulus, Sidney D. Drell, David Ritz Finkelstein, Laszlo Grenacs, Donal Hurley, Giuseppe La Rocca, Siegmund Levarie, Bernd Lindemann, Giulio Maltese, Wolfgang K.H. Panofsky, Orietta Pedemonte, Patricia Radelet-de Grave, Luigi A. Radicati di Brozolo, Michael Vandyck, Piero Villaggio, Kim Williams. Truesdell and the History of the Theory of Structures -- Reflections on Interdisciplinarianism -- The Sciences -- David Speiser’s Group Theory: From Stiefel’s Crystallographic Approach to Kac-Moody Algebras -- Whither Quantum Theory? -- The Direct Determination of the Induced Pseudoscalar Current (and About the Slow Metamorphosis of an Institution) -- In Praise of Asymmetry -- An Observation About the Huygens Clock Problem -- The History of Science -- Daniel Bernoulli and Leonhard Euler on the Jetski -- On the Changing Fortune of the Newtonian Tradition in Mechanics -- Studies of Magnetism in the Correspondence of Daniel Bernoulli -- On Enriques’s Foundations of Mechanics -- On the Common Origin of Some of the Works on the Geometrical Interpretation of Complex Numbers -- The Arts -- Architecture and Music -- An Unusual Sacra Conversazione by Giovanni Bellini -- Ancient Astrological and Musical Analogies in The Renaissance: Palladio’s Villa Rotunda and a Geometric Construction by Leonardo -- Nuclear Arms -- The Gravest Danger: Nuclear Weapons And Their Proliferation -- Nuclear Arms Control.